Study of Intrinsic and Extrinsic Factors with Diabetes Mellitus Classification - Novita, Anisah; Marniati, Marniati; Husna, Arfah; Iskandar, Iskandar; Putranto, Rudi Hendro; Putri, Enda Silvia; Anwar, Sufyan (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2022)
Diabetes mellitus is a group of metabolic diseases characterized by chronic hyperglycemia due to defects in insulin secretion, insulin action or both. The purpose of this study was to determine the relationship between intrinsic and extrinsic factors with the classification of diabetes mellitus. This research method is an analytic survey, with a cross sectional approach. The population is the entire number of outpatient diabetes mellitus patients as many as 4,365 people in 2019 and the sample in this study was 98 respondents, the sampling technique used a random sampling technique, analyzed univariate and bivariate using the chi-square test. The results showed that there was a significant relationship between social environmental factors (P-value: 0.000<0.05), cultural and religious environmental factors (P-value: 0.012<0.05), economic environmental factors (P-value: 0.037<0 0.05), emotional association factor (P-value: 0.000 < 0.05), physical and psychological state factors (P-value: 0.021<0.05), more assessment factor on food quality (P-value: 0.021<0.05) with the classification of diabetes mellitus. We are recommended for patients to take treatment as directed by health workers by using the 3J technique, namely paying attention to the type of food, amount of food and meal schedule to control blood sugar levels to avoid complications due to diabetes mellitus.